Kimura’s disease: A case report of recurring multiple swellings in the periauricular region - Bista, Meera; Bista, Raunak; Lakhey, Mamata; Gautam, Shirjan (Journal of Kathmandu Medical College, 2023)
Kimura’s disease is a rare, benign chronic inflammatory disorder that manifests with abnormal proliferation of vascular endothelium and lymphoid tissues. Ten years back, then 15-year-old Nepali (Asian) male presented to the otorhinolaryngology department with swelling of approximately 5 cm x 6 cm on the left and 6 cm x 7 cm on the right post-auricular region. The patient consulted for cosmetic reasons. Fine-needle aspiration cytology revealed Kimura’s disease. A high index of suspicion is needed to diagnose this disease. Early diagnosis can have proper treatment and treatment of co-existing conditions related to this disease.